Text Summarizing In Polish - Emilia Branny (Computer Science, 2005)
The aim of this article is to describe an existing implementation of a text summarizer forPolish, to analyze the results and propose the possibilities of further development. Theproblem of text summarizing has been already addressed by science but until now there hasbeen no implementation designed for Polish. The implemented algorithm is based on existingdevelopments in the ﬁeld but it also includes some improvements. It has been optimized fornewspaper texts ranging from approx. 10 to 50 sentences. Evaluation has shown that it worksbetter than known generic summarization tools when applied to Polish.